Mainstreaming systems approaches to support transitions towards resilient and sustainable farm and food systems in marginal environments: Better designing and targeting of interventions, informing policies and investments - Kumar, Shalander (International Crops Research Institute for the Semi-Arid Tropics, 2025)
Current agri-food systems face multiple challenges including climate risks, resource degradation, and persistent malnutrition affecting over 3 billion people globally. In India, despite running the world's largest public distribution system, 35% of children remain stunted and 67% are anemic. Agriculture contributes 18% to GDP but employs 44% of the workforce, with average farm household income remaining low at INR 10,218 per month. The high heterogeneity in smallholder farming systems—in resources, risks, and capacity—requires systems-based approaches for effective intervention design. Evidence from Maharashtra and Telangana shows significant yield gaps and heterogeneous outcomes even within the same geography. The systems approach enables targeted interventions by understanding feedback loops, analyzing vulnerability patterns, and identifying leverage points from household to landscape scales. Key pathways forward include crop diversification toward nutritious commodities, payment for ecosystem services, strengthening local food systems, and harnessing digital innovations for market integration.